A Review on Mosquitocidal Activity of Botanical Seed Derivatives - A. Shaalan, Essam; V. Canyon, Deon (Current Bioactive Compounds, 2015)
Diseases that are vectored by mosquitoes, such as malaria and dengue, have important associated economic impacts in countries with tropical and subtropical climates because they have significant detrimental impacts on the workforce. Decreasing susceptibility and resistance have been ever-present threats since the introduction of synthetic insecticides. Compounding this is our inability to identify or create new major classes of pesticides since the discovery of pyrethroids. Plants rich in bioactive biodegradable phytochemicals of less toxicity to the environment are thought to provide the solution. This review specifically examines available research on the mosquitocidal activity of eighty-one species of plant seeds. The essential oils from seeds were found to demonstrate a range of larvicidal, adulticidal, growth regulating, ovicidal, oviposition deterrent, and repellent activities. The lethal concentrations and toxicity of more highly active botanicals are comparable to those of organophosphates, which makes them potential candidates for future laboratory investigation and field evaluation.
Keywords: mosquitocidal activity